DETERMINANTS OF THE QUALITY OF OPERATING SEGMENT DISCLOSURE - Arina Adilla Hidayat; Mekani Vestari (Jurnal Akademi Akuntansi, 2021)
The Indonesian government encourages the manufacturing sector to diversify its business. The operating segments disclosures will be more important. Meanwhile, the provisions regarding this disclosure are still voluntary. There are several studies in Indonesia. However, the proxies used do not reflect the quality of the operating segment disclosures comprehensively. Therefore, this study aims to get empirical evidence on the determinants of the quality of operating segment disclosure by using Reporting Quality Index. The population was manufacturing companies listed on the IDX for 2015 - 2018. The data analysis technique uses multiple linear regression. The results show that firm size, leverage, degree of internationalization, and audit quality have a positive effect, while industry competition, profitability, and company growth have no effect on the quality of disclosure in the operating segment. This implies that external pressures have higher impact.